Mikroenkapsulasi Parasetamol Dengan Polimer Hidroxy Prophyl Methyl Celluloce (HPMC) Menggunakan Metoda Penguapan Pelarut - Rieke Azhar; Elva Yunengsih; Auzal Halim (STIFARM Padang, 2010)
The study on paracetamol microencapsulation by solvent evaporation method using hidroxy prophyl methil celluloce (HPMC) as a polimer has been done. The paracetamol Quantitation by UV spectrofotometer at 243 nm, using phosphate buffer pH 5,8 as the dissolution medium. The result showed that 1st formula’s dissolution rate is higher than 2nd and 3nd formulas, because the HPMC content of those formula are higher than the 1st formula, so paracetamol as a core are coored thicker, so that lower in drug rate releasing. The kinetic releasing mechanism of active ingredient from the microcapsule following the zero order, first order and Higuchi equation.